1964
DOI: 10.1002/hlca.19640470517
|View full text |Cite
|
Sign up to set email alerts
|

Ein neues Diterpen aus Salvia officinalis L. und eine Notiz zur Konstitution von Pikrosalvin

Abstract: Aus den Blättern von Salvia officinalis L. konnte eine neue Diterpen‐diphenol‐carbonsäure (äls Diacetylverbindung) isoliert und in ihrer Konstitution aufgeklärt werden. Durch eine relativ einfache und übersichtlich verlaufende Reaktionsfolge liess sich eine Verknüpfung rnit dem in derselben Pflanzenart von BRIESKORN et al. aufgefundenen Pikrosalvin erzielen, womit die von diesen Autoren postulierte Konstitution XIII (vgl. [6]) für Pikrosalvin im Sinne der Formel XIV modifiziert werden sollte. Pikrosalvin selbs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

1965
1965
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…The known abietane diterpenes were identified as carnosol (1), 20-deoxo carnosol (2), carnosic acid (3), 20-hydroxyferruginol (4), 12-O-methyl carnosic acid (5), and 11,12,20-trihydroxy-abieta-8,11,13-triene (6) (Fig. 1) by comparison with spectral data (UV, ESI-MS, and 1D and 2D NMR) of authentic samples and/or previous reports (Brieskorn and Fuchs, 1962;Linde, 1964;Inatani et al, 1982;Matsumoto and Usui, 1982;Gonzalez et al, 1988Gonzalez et al, , 1991Schwarz and Ternes, 1992;Cuvelier et al, 1994;Richheimer et al, 1996;Son et al, 2005). 20-Hydroxyferruginol was first isolated from Sequoia sempervirens (redwood) and shown to possess anti-tumour activity but has not previously been reported from Salvia officinalis (Son et al, 2005).…”
Section: Identification Of Isolated Metabolitesmentioning
confidence: 75%
“…The known abietane diterpenes were identified as carnosol (1), 20-deoxo carnosol (2), carnosic acid (3), 20-hydroxyferruginol (4), 12-O-methyl carnosic acid (5), and 11,12,20-trihydroxy-abieta-8,11,13-triene (6) (Fig. 1) by comparison with spectral data (UV, ESI-MS, and 1D and 2D NMR) of authentic samples and/or previous reports (Brieskorn and Fuchs, 1962;Linde, 1964;Inatani et al, 1982;Matsumoto and Usui, 1982;Gonzalez et al, 1988Gonzalez et al, , 1991Schwarz and Ternes, 1992;Cuvelier et al, 1994;Richheimer et al, 1996;Son et al, 2005). 20-Hydroxyferruginol was first isolated from Sequoia sempervirens (redwood) and shown to possess anti-tumour activity but has not previously been reported from Salvia officinalis (Son et al, 2005).…”
Section: Identification Of Isolated Metabolitesmentioning
confidence: 75%
“…The activities of rosemary and sage extracts are mainly due to a group of phenolic diterpenes and other phenolic acids such as rosmarinic and caffeic acids. The first PDAs isolated were carnosic acid (1) and carnosol (2) (Briekorn et al, 1964;Linde, 1964), which are also the best known, but the structures of other highly active compounds have since been elucidated, among others rosmanol (Inatani et al, 1982;Nakatani and Inatani, 1983), epirosmanol and isorosmanol (Nakatani and Inatani, 1984), rosmadial (4) (Nakatani and Inatani, 1983), methyl carnosate (7) (Cuvelier et al, 1994a) and rosmanol-9-ethyl ether (Djarmati et al, 1991), generically indicated as gand d-lactone PDAs (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Together with przewalskin ( 2 ), yunnanin A ( 3 ), and carnosol ( 4 ), elevenol ( 1 ) belongs to a group of 7–20 oxa-bridged dinorditerpenes and diterpenes. According to the majority of publications in this area the abietane based numbering illustrated in the common basic structure 5 is used within this work.…”
mentioning
confidence: 99%